Perioperative Factors Associated With Chronic Central Pain After the Resection of Intramedullary Spinal Cord Tumor. Issue 7 (July 2017) - Onishi-Kato, Yuki; Nakamura, Masaya; Iwanami, Akio; Kato, Masayoshi; Suzuki, Takeshi; Kosugi, Shizuko; Katori, Nobuyuki; Hashiguchi, Saori; Tsuzaki, Koichi; Takeda, Junzo; Morisaki, Hiroshi
Abstract : Objective: Some patients experience severe chronic pain after intramedullary spinal cord tumor (IMSCT) resection, but the underlying mechanisms have yet to be fully elucidated. We aimed to investigate perioperative factors associated with chronic pain after IMSCT resection. Materials and Methods: We analyzed data from a postal survey and the medical records of patients who had undergone IMSCT resection in our institution between 2000 and 2008. Chronic pain was assessed using the Neuropathic Pain Symptom Inventory score, and its associations with factors related to tumor pathology, patient demographics, neurological findings, surgery, anesthesia, and perioperative management were determined. Results: Seventy-eight consecutive patients (55 men and 23 women; age 17 to 79 y) were included in the statistical analysis of the present study. In univariate analyses, sex, body mass index, preoperative tumor-related pain, preoperative nonsteroidal anti-inflammatory drugs, intraoperative hypotension, postoperative corticosteroids, and decrease in Japanese Orthopaedic Association (JOA) scores were found to be associated with postsurgical chronic central pain. Logistic regression analysis identified 3 significant factors: a decline in JOA scores compared with preoperative values (odds ratio [OR], 3.33; 95% confidence interval [CI], 1.18-9.42; P =0.023), intraoperative hypotension (OR, 3.01; 95% CI, 1.02-8.97; P =0.047), and postoperative corticosteroids (OR, 3.21; 95% CI, 1.02-10.09; P =0.046). Discussion: Decline in JOA score, intraoperative hypotension, and postoperative corticosteroids are independently associated with postsurgical chronic central pain. Intraoperative hypotension and the use of postoperative corticosteroids can be avoided or modified during perioperative management. As results from animal studies have indicated that the administration of corticosteroids may intensify chronic pain, further studies in larger cohorts are required to definitively determine the effect of corticosteroids on postsurgical central pain. Abstract : Supplemental Digital Content is available in the text.